2000
DOI: 10.1136/pmj.76.899.574
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin induced avascular necrosis of head of femur

Abstract: Chemically induced avascular necrosis of bone is a well documented entity. Indomethacin is one of the causes of this condition but is often diYcult to recognise. Review of the literature shows that only one case of indomethacin induced avascular necrosis has been reported in the English language between 1966 and the present.The case of a young healthy man, who developed avascular necrosis of head of femur after prolonged administration of indomethacin, is reported here. (Postgrad Med J 2000;76:574-575)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…We found none of the inflammation-related signaling pathways, such as the TNF-α and the NF-κB signaling pathways, were significantly enriched when an adjusted P -value < 0.05 was considered statistically significant. Moreover, our investigation revealed that certain non-selective non-steroidal anti-inflammatory drugs (NSAIDs) had been reported to be associated with the development of ONFH, such as diclofenac 15 and indomethacin 16 . These unexpected findings suggest that non-selective NSAIDs, commonly prescribed to alleviate pain in patients with ONFH, may pose medication risks that have not been given due attention by orthopedic surgeons 4 .…”
Section: Discussionmentioning
confidence: 93%
“…We found none of the inflammation-related signaling pathways, such as the TNF-α and the NF-κB signaling pathways, were significantly enriched when an adjusted P -value < 0.05 was considered statistically significant. Moreover, our investigation revealed that certain non-selective non-steroidal anti-inflammatory drugs (NSAIDs) had been reported to be associated with the development of ONFH, such as diclofenac 15 and indomethacin 16 . These unexpected findings suggest that non-selective NSAIDs, commonly prescribed to alleviate pain in patients with ONFH, may pose medication risks that have not been given due attention by orthopedic surgeons 4 .…”
Section: Discussionmentioning
confidence: 93%